The Implementation of Entrepreneurship Education to Improve Students' Life-Skills in an Islamic Boarding School - Ulfa, Fitriana; Firdausa, Royyana (Tadibia Islamika: Journal of Holistic Islamic Education, 2021)
This study has three primary objectives: Firstly, to analyze the entrepreneurship education plan's role in enhancing the life skills of students at the Walindo Manba'ul Falah Islamic Boarding School in Pekalongan Regency. Secondly, to examine the practical implementation of entrepreneurship education for life skill development at the same institution. And finally, to assess the evaluation process of entrepreneurship education's effectiveness in fostering life skills among students at the Walindo Manba'ul Falah Islamic Boarding School in Pekalongan Regency. To achieve these goals, a qualitative approach was employed, involving data collection through methods such as observation, interviews, and documentation. In-depth interviews were conducted with various stakeholders, including boarding school caregivers, Islamic boarding school leaders, coordinators of pesantren business units, and business unit managers. Data analysis techniques encompassed data reduction, data presentation, and the derivation of conclusions. To ensure data validity, triangulation of sources and techniques was used, complemented by established theoretical frameworks. The findings of this research reveal three key insights. Firstly, the planning of entrepreneurship education at the Walindo Manba'ul Falah Islamic boarding school in Pekalongan Regency is executed through two distinct approaches: practice-based planning and planning via the hidden curriculum. Secondly, in practice, entrepreneurship education at the institution follows a "learning by doing" educational model, wherein students actively participate in managing the pesantren's business units as a means of experiential learning. Thirdly, the evaluation of entrepreneurship education at the Walindo Manba'ul Falah Islamic boarding school in Pekalongan Regency comprises a comprehensive assessment encompassing input, process, and output (product) aspects.